Analyzing the Professional Satisfaction and Organisational Identification in Football Referees - Yeşim BAYRAKDAROĞLU; Yavuz ÖNTÜRK; Üstün TÜRKER; Mustafa AYHAN; Mahir KAPLAN; Büşra UYAR ŞAFAK (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi)
This study aims to analyze the Professional satisfaction and organizational identification of football referees within the Turkish Football Federation and to explore the relationship between these concepts. The research employed a descriptive survey model, sampling 151 referees (129 males, 22 females) from the Black Sea region. The "Professional Pleasure Scale for Referees" (OHSR) developed by Karaçam and Pulur (2018) and the "Organizational Identification Scale" (OAS) created by Mael and Ashforth (1992), which was adapted into Turkish by Tak and Aydemir (2004), were utilized for data collection. The statistical analyses conducted comprised One Sample Kolmogorov-Smirnov, Mann Whitney U, Kruskal Wallis H, and Spearman Correlation. The findings demonstrate higher levels of professional satisfaction and organizational identification among referees. A statistically significant and positive relationship was identified between these two variables (p < 0.05). Further analysis indicated that male referees exhibited significantly higher levels of organizational identification in comparison to their female counterparts, whereas no significant differences in professional satisfaction were observed between genders. Referees holding a bachelor's degree demonstrated greater professional satisfaction than their counterparts with associate or postgraduate degrees. Class A referees exhibited a greater level of organizational identification compared to those in lower classifications. Referees who expressed contentment with their assignment frequency and income levels indicated a significant increase in professional satisfaction and organizational identification. The findings indicate that demographic and professional factors, including gender, education level, classification, and income satisfaction, have a significant impact on referees' professional satisfaction and organizational commitment. The study emphasizes the necessity for customized interventions to improve referees' work experiences, indicating that enhanced training and support systems may significantly influence their satisfaction and professional identity.